Experimental and analytical investigation on the flow characteristics in an open natural circulation system. (September 2017) - Hou, Xiaofan; Sun, Zhongning; Fan, Guangming; Wang, Lu
Highlights: The open natural circulation flow behaviors are studied by experiment. The individual characteristics of flashing and boiling are obtained by linear model. The interaction mechanisms of flashing and boiling are found out. The evolution mechanisms of open natural circulation flow behavior are figured out. The measures to form steady flashing flow are put forward based on above mechanism. Abstract: The open natural circulation has been widely used in the designs of advanced nuclear reactor in recent years due to its inherent safety. In this paper, an experimental and analytical investigation was carried out in an open natural circulation loop, to figure out the mechanism of the open natural circulation behaviors. The experimental result showed six different flow modes occur in the loop. There into the mode of steady flashing flow is newly discovered, and it cannot be formed spontaneously in our experiment. Moreover, it is observed from those flow modes that the boiling and the flashing interact with each other strongly, and determine the behaviors of open natural circulation separately or jointly. Therefore, the open natural circulation behavior can be considered as interaction results of flashing and boiling. To figure out the interaction mechanism, a linear model was conducted to investigate the instability regions caused by only flashing and only boiling respectively. By comprehensive comparing the experimental results and analytical results, the mechanism of the interaction between flashing and boiling, and how the flashing and boiling influence the open natural circulation behaviors were figured out. Moreover, according to those mechanisms, the measurements to form the steady flashing flow are also put forwards.